Influence of some technological factors upon wall ceramics frost resistance - Bołtryk, Michal; Nikitin, Vadim; Backiel‐Brzozowska, Beata (Journal of Civil Engineering and Management, 2004)
A polynomial model, which enables evaluation of the influence of amount and graining of sand in a ceramic mix and maximum temperature and duration of burning upon ceramics frost resistance, constructed on the basis of experimental results is presented in this work. During the experiment the mass loss of ceramic specimens was measured. Experimental results were prepared for further statistical analysis with regard to linear summing of mass losses. Statistical evaluation of the quality of the constructed model and physical interpretation of tested factors were made. In addition, the authors presented the results of the samples bulking investigation in comparison with the results of frost‐resistance test. Also the correlation of the results of both investigations was checked.First Published Online: 14 Oct 2010